Phenotypic spectrum in recessive STING-associated vasculopathy with onset in infancy: Four novel cases and analysis of previously reported cases - Wan, Rensheng; Fänder, Johannes; Zakaraia, Ia; Lee-Kirsch, Min Ae; Wolf, Christine; Lucas, Nadja; Olfe, Lisa Isabel; Hendrich, Corinna; Jonigk, Danny; Holzinger, Dirk; Steindor, Mathis; Schmidt, Gunnar; et al. (Frontiers in Immunology, 2022)
Gain-of-function variants in the stimulator of interferon response cGAMP interactor 1 (STING1) gene cause STING-Associated Vasculopathy with onset in Infancy (SAVI). Previously, only heterozygous and mostly de novo STING1 variants have been reported to cause SAVI. Interestingly, one variant that only leads to SAVI when homozygous, namely c.841C>T p.(Arg281Trp), has recently been described. However, there are no entries in public databases regarding an autosomal recessive pattern of inheritance. Here, we report four additional unrelated SAVI patients carrying c.841C>T in homozygous state. All patients had interstitial lung disease and displayed typical interferon activation patterns. Only one child displayed cutaneous vasculitis, while three other patients presented with a relatively mild SAVI phenotype. Steroid and baricitinib treatment had a mitigating effect on the disease phenotype in two cases, but failed to halt disease progression. Heterozygous c.841C>T carriers in our analysis were healthy and showed normal interferon activation. Literature review identified eight additional cases with autosomal recessive SAVI caused by c.841C>T homozygosity. In summary, we present four novel and eight historic cases of autosomal recessive SAVI. We provide comprehensive clinical data and show treatment regimens and clinical responses. To date, SAVI has been listed as an exclusively autosomal dominant inherited trait in relevant databases. With this report, we aim to raise awareness for autosomal recessive inheritance in this rare, severe disease which may aid in early diagnosis and development of optimized treatment strategies.